Karrierutak, különös tekintettel a patchwork-re - Gulyás, László (Közép-Európai Közlemények, 2016)
Nowadays the growing part of literature of human resource management is carrier-papers books. The carrier and related area –as an important part of HRM –can be investigated from two point of view. One is the view of organism, which is called carrier-management by the literature. It means that the employer gives the carrier opportunity to personnel according to their talent.The other view investigates the carrier from the view of individual. According to this carrier is the sequence of positions, grading higher and higher. The first part of recent essay is dealing with the features of traditional carrier ways. The second part of recent essay surveys the patchwork career.